New exercise model in Sepaktakraw Games - Aji, Tri; Achmad Sofyan Hanif,; Humaid, Hidayat; Jufrianis, (Technium Social Sciences Journal, 2020)
The research and development of this model aims to improve the achievements of sepaktakraw sports with a new sports training model in sepaktakraw games. The research method used is a method of research and development with development measures designed by Borg and Gall with the number of populations and samples in this study is as many as 65 sepaktakraw athletes central java covering jepara, kendal and semarang areas.. Based on the processing of data with statistical science with a total sample of 65 sepaktakraw athletes in can grade Bbased on theeffectiveness test results using t-test of the difference of pretest results obtained price tO = 150,338 greater than the price tt =0,000 and the posttest value obtained price tO = 197,550 greater than the price tt = 0,000 (at the level of significance 0.05), then the nil hypothesis is rejected. So it can be concluded that, there is a significant difference between the pretest and posttest test results of the new game practice model in sepaktakraw games. From the research data obtained the average pretest price with mean = 85,533 smaller than the average posttest mean = 92,233. Thus it can be stated that, the product of a new game training model in sepaktakraw games is effectively used to improve the achievements of sepaktakraw athletes in indonesia. Thus it can be stated that, the product of a new sports model in sepaktakraw games is effectively used to improve the achievements of takraw football athletes in Central Java in particular, and nationally as well as internationally in general